The Decline in Demand for Unskilled Labor: An Empirical Analysis Method and its Application to France - Goux, Dominique; Maurin, Eric (The Review of Economics and Statistics, 2000)
The decline in the unskilled share of French employment is chiefly due to the slackness of domestic demand for those industries with the highest proportion of unskilled workers. The spread of computers has not been particularly conducive to substitution between skilled and unskilled labor. We test and accept the hypothesis of technical-progress neutrality within French industries. The mechanisms that generate inequality do not appear to be the same in France and in the United States. The source of inequality isn't so much technical progress per se as its interaction with the institutions that regulate the labor market.